Escaping the middle-income trap: A study on a developing economy - Islam, Md. Jaber Al; Mahmud, Imroz; Islam, Aminul; Sobhani, Farid Ahammad; Hassan, Md. Sharif; Ahsan, Arif (Cogent social sciences, 2023)
Middle-Income Trap (MIT) is a phenomenon wherein a nation finds itself unable to progress from a middle-income status to a high-income economy. Despite Bangladesh's rapid economic growth as a developing economy following its transition to the lower-middle-income category, the country faces various economic challenges that may impede its advancement to higher-income tiers. Consequently, this study delves into whether Bangladesh can successfully navigate its way out of the lower-middle-income and upper-middle-income traps. To assess this, the study initially employed a time threshold method known as the "Number of Years Method." It determined that Bangladesh is poised to break free from the lower-middle-income and upper-middle-income traps by 2029 and 2041, provided the nation can sustain a per capita Gross National Income (GNI) growth rate of 9.69%. To further evaluate the sustainability of this income growth, the study utilized three quantitative approaches: Catch-up Growth, Growth Report, and Growth Acceleration. Interestingly, these methods yielded contrasting results. The insights generated by this study hold significance for economists and policymakers in Bangladesh and other developing economies facing similar challenges. These findings enable them to assess the likelihood of becoming ensnared in the middle-income trap and, as a result, formulate appropriate strategies to overcome it.